Neurodevelopmental outcome following cerebellar tumour sustained in early childhood - Davis, Emma E. (2011)
Mounting evidence from imaging studies, developmental disorders and typically-developing children suggests that different domains of functioning are more closely related than previously considered. This is reflected in theories of development which are increasingly recognising that developmental progression should be considered as an integrated process, with associations between domains. The extent of the interrelation between cognitive and motor skills remains unclear despite previous investigations. Examination of this relationship in typically-developing children is important to clarify the nature of this link, thereby informing theories of development for both typical and atypical populations. This thesis investigated the underlying nature of the association between cognitive and motor domains to establish the extent of interrelation and whether this link alters across development. As the cerebellum has been hypothesised to be instrumental in this relationship (Diamond, 2000), the role of the cerebellum was investigated by examining cognitive and motor development in children treated for cerebellar tumour in the preschool years (N=15). The impact of cerebellar injury on development of scholastic and attentional skills was also investigated, together with the influence of factors affecting prognosis. The interrelation of cognitive and motor skills in typically-developing children (N=248; 4-11 years) was found to be underpinned by a link between visual processing abilities and fine manual motor skills. Despite fluctuations in correlations between other aspects of cognitive and motor functioning, this core relationship remained constant, furthering evidence that cognitive and motor development are linked from an early age. A similar pattern of correlations was seen for the patient sample, suggesting that development in these domains remains tightly linked despite damage to an underlying component of the anatomical network. This suggests that the patients are demonstrating a developmental delay, rather than deviation; their trajectory does not appear to be qualitatively different from that of typically-developing children, rather development appears to be more constrained than suggested by some hypotheses (e.g. Karmiloff-Smith, 1992). Cerebellar damage was therefore found to impact on the two domains similarly, offering support to a „universal cerebellar transform‟ (Schmahmann, 2000b) conceptualisation of cerebellar functioning. Both cognitive and motor skills were found to be compromised following a cerebellar tumour, although no specific impact of cerebellar damage was reported on scholastic skills, above and beyond general cognitive deficit. Attention was found to be impaired in the patient sample, with sustained attention most closely related to functioning in cognitive, academic and motor skills, suggesting that a deficit in this basic underlying process underlies difficulties in other domains. In addition, sustained attention was implicated in the association between visual processing and fine manual control in the patient sample, suggesting that this core link may be further underpinned by more basic cognitive processes. Effective rehabilitation may therefore target sustained attention, as this appears to be related to functioning in the other domains assessed in this study, as well as recognising that an integrated approach across domains is likely to yield maximum benefits. Of the potential moderating factors investigated, age at diagnosis and tumour type/treatment were found to be the most reliable predictors of outcome. This research highlights the importance of a case-study approach, and the clinical importance of individual investigation of each child‟s needs for rehabilitation.